Against the Wall: Ideology and Form in Mies van der Rohe's Monument to Rosa Luxemburg and Karl Liebknecht. Issue 1 (2nd January 2017) - Chapman, Michael
Abstract : This essay looks at Mies van der Rohe's 1926 Monument to Rosa Luxemburg and Karl Liebknecht from the perspective of contemporaneous theories of Marxism, and particularly those of Luxemburg herself. The essay sets out to explore the political backdrop against which the monument was made, Mies's own political allegiances at the time, and the symbolic and spatial implications of this influential architectural monument. The essay reflects on the relationship between avant-garde practices and Marxism, and the role of ideology in framing certain practices within architectural modernism.